Conformity of Planning and Budgeting Documents for Regional Government Budgets (APBD) at the Regional Research and Development Planning Agency of Kotamobagu City - Wijayanti, Ari Trisna; Mamonto, Fitri; Bulo, Laurens (Technium Social Sciences Journal, 2025)
The main objectives of this study are to determine, analyze and describe the suitability of planning and budgeting documents for the Regional Government Budget (APBD) at the Regional Research and Development Planning Agency of Kotamobagu City and to determine, analyze and describe the determinants of the suitability of planning and budgeting documents for the APBD at the Regional Research and Development Planning Agency of Kotamobagu City. The approach used in this research is a qualitative approach with a research focus on the suitability of APBD planning and budgeting documents at the Regional Research and Development Planning Agency of Kotamobagu City and the determinants of the suitability of APBD planning and budgeting documents at the Regional Research and Development Planning Agency of Kotamobagu City. The results showed that the harmonization of planning documents from the regional and central levels was carried out with adjustments through consistency of the main objectives of regional planning with national main objectives, consistency of policy directions and regional development strategies that support national priorities, conformity of targets with national priority targets, and adjustments to allocated funding. Factors that hinder the suitability of APBD planning and budgeting documents are central government policies that have a very significant effect on the suitability of planning and budgeting documents and DPRD intervention. Thus, a commitment is needed between the local government and the legislature to maintain the suitability of planning and budgeting.